Pharmacokinetics of oxycodone/naloxone and its metabolites in patients with end-stage renal disease during and between haemodialysis sessions. Issue 4 (5th September 2018) - Leuppi-Taegtmeyer, Anne; Duthaler, Urs; Hammann, Felix; Schmid, Yasmin; Dickenmann, Michael; Amico, Patricia; Jehle, Andreas W; Kalbermatter, Stefan; Lenherr, Christoph; Meyer zu Schwabedissen, Henriette E; Haschke, Manuel; Liechti, Matthias E; et al.
Abstract: Background: The pharmacokinetics of oxycodone in patients with end-stage renal disease (ESRD) requiring haemodialysis are largely unknown. Therefore, we investigated the pharmacokinetics of oxycodone/naloxone prolonged release and their metabolites in patients with ESRD during and between haemodialysis sessions. Methods: Single doses of oxycodone/naloxone (5/2.5 or 10/5 mg) were administered in nine patients with ESRD using a cross-over design on the day of dialysis and on a day between dialysis sessions. Plasma, dialysate and urine concentrations of oxycodone, naloxone and their metabolites were determined up to 48 h post-dosing using a liquid chromatography–tandem mass spectrometry system. Results: Haemodialysis performed 6–10 h after dosing removed ∼10% of the administered dose of oxycodone predominantly as unconjugated oxycodone and noroxycodone or conjugated oxymorphone and noroxymorphone. The haemodialysis clearance of oxycodone based on its recovery in dialysate was (mean ± SD) 8.4 ± 2.1 L/h. The geometric mean (coefficient of variation) plasma elimination half-life of oxycodone during the 4-h haemodialysis period was 3.9 h (39%) which was significantly shorter than the 5.7 h (22%) without haemodialysis. Plasma levels of the active metabolite oxymorphone in its unconjugated form were very low. Conclusions: Oxycodone is removed during haemodialysis. The pharmacokinetics including the relatively short half-life of oxycodone in patients with ESRD with or without haemodialysis and the absence of unconjugated active metabolites indicate that oxycodone can be used at usual doses in patients requiring dialysis.